Optimalisasi Parimeter Di Wilayah Airside Di Bandar Udara Oesman Sadik Labuha Terhadap Keamanan Penerbangan - Mustafa, Nafsiah Hi; Nanik Rianandita Sari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Airports play a crucial role in the transportation system, linking flights with ground transportation and supporting the global economy. Flight safety is a top priority, and one important aspect of ensuring it is the optimization of the perimeter in the airport's airside area. At Oesman Sadik Airport, there is an issue with inadequate runway fencing, which causes the public to frequently approach the runway and threaten flight safety. This study aims to identify the constraints in optimizing the perimeter in the airside area of Oesman Sadik Airport and provide recommendations to enhance the security system for better flight safety.This study uses a descriptive qualitative method to evaluate perimeter optimization in the airside area of Oesman Sadik Airport in September 2023. The subjects are airport employees, and the object of the study is the perimeter system itself. Primary data is collected through interviews and observations, while secondary data includes documents such as SOPs and airport maps. Data analysis involves reduction, presentation, and verification. Data validity is tested using source and method triangulation. The research steps include observation, problem identification, planning, data collection, analysis, and conclusion.The results show that steps for optimizing the perimeter at Oesman Sadik Airport include utilizing advanced technology, enhancing security personnel, and physical improvements to significantly improve flight safety. Addressing the constraints in optimization requires a structured approach, including a thorough evaluation of security needs, efficient resource allocation, strong partnerships with relevant parties, and the implementation of innovative and adaptive solutions to face technical and environmental security challenges at the airport.